PENGARUH PEMILIHAN JARAK KOLOM PADA STRUKTUR RANGKA PEMIKUL MOMEN KHUSUS BETON TERHADAP BIAYA - Royhan Fanany; Bantot Sutriono (LPPM Universitas Bina Bangsa, 2023)
With the addition of the building design age does not only rely on the resistance of the building to the load. Many developments requests lead to buildings that are economical, strong, and according to architectural wishes. In this study, we will compare the effect of column spacing on special moment-bearing frame structures on costs. The method used is to compare 3 buildings with the long span of Building A 3m, Building B 4m and Building C 6m. The three buildings will be compared against Displacement, Building Prices and Structural Performance. From the results of the study, the overall price of the building in Building A (Rp 6,333,433,690) occupies the highest price of the other buildings, followed by Building B (Rp 5,333,852,309), and Building C (Rp 4,362,303,657), Base Force in Building A ( 21833 kN, and 21283 kN) have more resistance compared to other buildings followed by Building B (20010 kN and 19296 kN), and Building C (16348 kN and 15314 kN), and Building performance in Building C (IO) has a level security of the entire building followed by Building B (DC), and Building A (DC)